Targeted genetic analysis in a large cohort of familial and sporadic cases of aneurysm or dissection of the thoracic aorta. (November 2018) - Weerakkody, Ruwan; Ross, David; Parry, David; Ziganshin, Bulat; Vandrovcova, Jana; Gampawar, Piyush; Abdullah, Abdulshakur; Biggs, Jennifer; Dumfarth, Julia; Ibrahim, Yousef; Bicknell, Colin; Field, Mark; et al.
Abstract Purpose Thoracic aortic aneurysm/aortic dissection (TAAD) is a disorder with highly variable age of onset and phenotype. We sought to determine the prevalence of pathogenic variants in TAAD-associated genes in a mixed cohort of sporadic and familial TAAD patients and identify relevant genotype–phenotype relationships. Methods We used a targeted polymerase chain reaction and next-generation sequencing–based panel for genetic analysis of 15 TAAD-associated genes in 1, 025 unrelated TAAD cases. Results We identified 49 pathogenic or likely pathogenic (P/LP) variants in 47 cases (4.9% of those successfully sequenced). Almost half of the variants were in nonsyndromic cases with no known family history of aortic disease. Twenty-five variants were withinFBN1 and two patients were found to harbor two P/LP variants. Presence of a related syndrome, younger age at presentation, family history of aortic disease, and involvement of the ascending aorta increased the risk of carrying a P/LP variant. Conclusion Given the poor prognosis of TAAD that is undiagnosed prior to acute rupture or dissection, genetic analysis of both familial and sporadic cases of TAAD will lead to new diagnoses, more informed management, and possibly reduced mortality through earlier, preclinical diagnosis in genetically determined cases and their family members.